Analysis of BPJS Patient Satisfaction in Inpatient of Regional General Hospital Tani & Nelayan of Boalemo Regency - Jufri Yusup; Arifin Tahir; Firdausi Ramadhani (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The purpose of this research are: 1) to find out and analyze the level of patient satisfaction from the aspect of BPJS Health service quality in the Inpatient Unit of the RSUD Tani dan Nelayan, Boalemo Regency seen from Service Requirements, Systems, Mechanisms and Service Procedures, Time of Completion, Service Costs, Product Specifications, Service Types, Competence Service Executor, Service Implementer Behavior, Complaint Handling Suggestions and Inputs, Facilities and Infrastructure; 2) to find out the factors that determine the satisfaction level of BPJS Healthcare patients in the Inpatient Unit of the RSUD Tani dan Nelayan, Boalemo Regency. The research method applied in this research is qualitative research with descriptive approach. This research was conducted at Tani and Nelayan Hospital Boalemo Regency. Primary data is obtained through direct interviews to competent parties in the patient's Family service to the satisfaction of BPJS patients at Tani and Nelayan Hospital Boalemo Regency. Secondary data of this research was obtained from documents at Tani and Nelayan Hospital boalemo regency. There are three flow of activities in analyzing it, namely data reduction, data presentation, and withdrawal of conclusions/verification. The results showed that: 1) satisfaction of BPJS healthcare patient at the Inpatient Unit of the Tani dan Nelayan Hospital of Boalemo Regency that the requirements, system of service mechanisms and procedures, time of completion, are in an orderly manner according to the provisions. Meanwhile, in terms of costs/rates, product specifications for the type of service, executive competence, implementation behavior, handling of complaints and suggestions, facilities, and infrastructure, the level of patient satisfaction is still low; 2) The factors that determine the satisfaction of BPJS Kesehatan patients at the Inpatient Unit of the Regional General Hospital of Farmers and Fishermen, Boalemo District, conclude that the quality of products/services, quality of service, emotional, price and cost determine patient satisfaction.